2021
DOI: 10.4018/ijwltt.294572
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual Education

Abstract: The purpose of the study is the research of the opportunities for developing professional foreign language communicative competence within the concept of multilingual education. The study is based on the method of the experiment, presented by a survey of students. The course was tested by 70 master's degree students of Gumilyov Eurasian National University. The functionality of the Google Meet communication platform and mobile applications has created a comfortable environment for learning Business English. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…At the same time, Alzhanova and Chaklikova (2022) emphasised the importance of adapting educational technologies to develop professional intercultural communicative competence. Notably, they fail to recognise broader sociological implications for local professors' dispositions, linguistic and pedagogical Habitus, and professional identities (Block et al, 2013;Bourdieu, 2000;Grenfell & James, 1998).…”
Section: Taking Stock Of the Kazakhstani Higher Education (He) Fieldmentioning
confidence: 99%
“…At the same time, Alzhanova and Chaklikova (2022) emphasised the importance of adapting educational technologies to develop professional intercultural communicative competence. Notably, they fail to recognise broader sociological implications for local professors' dispositions, linguistic and pedagogical Habitus, and professional identities (Block et al, 2013;Bourdieu, 2000;Grenfell & James, 1998).…”
Section: Taking Stock Of the Kazakhstani Higher Education (He) Fieldmentioning
confidence: 99%
“…However, these research differ in their motivations for examining educated groups and their methodologies. Using the Australian English Communicative Development Inventory (OZI), Caroline Jones et al Alzhanova & Chaklikova (2022) investigate multilingual education, whereas Olesia et al (2022) investigate language-learning tutorials based on intercultural and communicative techniques. Trevor & Elison (2022) explore lexical and syntactic acquisition, whereas Bardis (2021) analyses communicative dynamics in the classroom with a focus on cross-cultural pragmatic competence in English as a foreign language.…”
Section: Theory Integrationmentioning
confidence: 99%
“…The samples included students, teachers, and children of all ages. However, 16 studies found in favour of students: (Maksimuk et al, 2022;Olesia et al, 2022;Alzhanova & Chaklikova, 2022;Temirgalinova, et al, 2021;Bardis et al, 2021;Rongmei, 2020 ;Alcaraz-Mármol, 2020;Abugohar, Yassin, 2020;Mart, 2019;(2015;Lyubova et al, 2014;Jabeen, 2014;Sadykova et al, 2014;Sun, 2013;Zhongxin, 2013). Approximately (7) investigations on children followed (Jones et al, 2022;Trevor & Elison, 2022;Ramscar, 2021;Segovia-Martn & Balari, 2020;Mayor & Mani, 2019;Rytel, 2014;Fernanda, 2012).…”
Section: Type Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations